Genome-wide identification and analysis of glyceraldehyde-3-phosphate dehydrogenase family reveals the role of GmGAPDH14 to improve salt tolerance in soybean (Glycine max L.) - Zhao, Xunchao; Wang, Jie; Xia, Ning; Qu, Yuewen; Zhan, Yuhang; Teng, Weili; Li, Haiyan; Li, Wenbin; Li, Yongguang; Zhao, Xue; Han, Yingpeng (Frontiers in Plant Science, 2023)
Introduction Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is an essential key enzyme in the glycolytic pathway and plays an important role in stress responses. Although GAPDH family genes have been found in different plant species, the determination of their gene family analysis and their functional roles in soybean are still unknown. Methods In this study, gene sequence and expression data were obtained using online tools, and systematic evolution, expression profile analysis, and qRT-PCR analysis were conducted. Results and Discussion Here a total of 16 GmGAPDH genes were identified on nine chromosomes, which were classified into three clusters. Additionally, all GmGAPDH genes harbor two highly conserved domains, including Gp_dh_N (PF00044) and Gp_dh_C (PF02800). The qRTPCR analysis also showed that most GmGAPDH genes significantly responded to multiple abiotic stresses, including NaHCO3, polyethylene glycol, cold, and salt. Among them, GmGAPDH14 was extraordinarily induced by salt stress. The GmGAPDH14 gene was cloned and overexpressed through soybean hair roots. The overexpressed transgenic soybean plants of the GmGAPDH14 gene have also shown better growth than that of control plants. Moreover, the overexpressed transgenic plants of GmGAPDH14 gene had higher activities of superoxide dismutase but lower malonaldehyde (MDA) content than those of control plants under salt stress. Meanwhile, a total of four haplotypes were found for the GmGAPDH14 gene, and haplotypes 2, 3, and 4 were beneficial for the tolerance of soybean to salt stress. These results suggest that the GmGAPDH14 gene might be involved in the process of soybean tolerance to salt stress. The results of this study will be valuable in understanding the role of GAPDH genes in the abiotic stress response of soybean.